Dual Mechanisms of Coniferyl Alcohol in Phenylpropanoid Pathway Regulation - Guan, Mengling; Li, Changxuan; Shan, Xiaotong; Chen, Fang; Wang, Shufang; Dixon, Richard A.; Zhao, Qiao (Frontiers in Plant Science, 2022)
Lignin is a complex phenolic polymer that imparts cell wall strength, facilitates water transport and functions as a physical barrier to pathogens in all vascular plants. Lignin biosynthesis is a carbon-consuming, non-reversible process, which requires tight regulation. Here, we report that a major monomer unit of the lignin polymer can function as a signal molecule to trigger proteolysis of the enzyme L-phenylalanine ammonia-lyase, the entry point into the lignin biosynthetic pathway, and feedback regulate the expression levels of lignin biosynthetic genes. These findings highlight the highly complex regulation of lignin biosynthesis and shed light on the biological importance of monolignols as signaling molecules.